Mechanical Strength Properties of Resin-Coated Cardboard as a Viable Alternative to Glass Fiber in the Construction of Fiberglass Vessels - Yuwandana, Dwi Putra; Budiarti, Yesnina; Novita, Yopi; Komarudin, Didin (Kapal: Jurnal Ilmu Pengetahuan dan Teknologi Kelautan, 2025)
Fiberglass vessels produce considerable environmental waste due to the non-biodegradable nature of glass fiber materials, necessitating the exploration of biodegradable alternatives. Given the abundance of cardboard waste in Indonesia, this study investigates its potential as a substitute for glass fiber in fiberglass boat construction. In the process of producing cardboard sheets, during the pulping stage using a blender, the 716 grams of cardboard are mixed with 10 to 15 liters of water. The research aims to evaluate resin-coated cardboard's physical properties and mechanical strength, comparing them to the mechanical strength standards set by the Indonesian Classification Bureau (BKI). Utilizing an experimental methodology with descriptive and comparative analysis, the results indicate that resin-coated cardboard possesses robust, lightweight, and water-resistant characteristics. The four-layer treatment achieved the highest tensile strength and bending strength values of 37.61 MPa and 62.23 MPa, respectively. In comparison, the three-layer treatment yielded a maximum modulus of elasticity of 145.80 MPa. Although the mechanical properties did not meet the minimum standards established by BKI, the resin-coated cardboard demonstrates potential as an alternative material for plywood coatings in the superstructures of vessels.